2023
DOI: 10.1001/jamanetworkopen.2023.23200
|View full text |Cite
|
Sign up to set email alerts
|

Philadelphia Beverage Tax and Association With Prices, Purchasing, and Individual-Level Substitution in a National Pharmacy Chain

Abstract: ImportanceTaxes on sweetened beverages are being implemented around the globe; an understanding of these taxes on individual-level behavior is necessary.ObjectiveTo evaluate the degree to which the sweetened beverage tax in Philadelphia, Pennsylvania, was associated with changes in beverage prices and individual-level purchasing over time at a national pharmacy chain in Philadelphia compared with Baltimore, Maryland.Design, Setting, and ParticipantsUsing a difference-in-differences approach and generalized lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…In recent years, various policies and interventions have been implemented globally to reduce sugar intake and combat CVD ( 36 ). These efforts focus on taxation, regulation, and public health education ( 37 ). One prominent approach is the implementation of SSB taxes.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, various policies and interventions have been implemented globally to reduce sugar intake and combat CVD ( 36 ). These efforts focus on taxation, regulation, and public health education ( 37 ). One prominent approach is the implementation of SSB taxes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to selling alcohol and tobacco, some US pharmacies also sell and endorse (through promotional pricing) sugar-sweetened beverages (SSBs) [ 13 , 152 , 153 , 154 ], creating a potential negligence to protect their customers, given a growing body of evidence that SSB consumption can increase both mortality and morbidity risks [ 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 ]. National pharmacy chains can reach SSB sales of estimated 100 million transactions per year ( Figure S2, Supplementary Materials ).…”
Section: Pharmacies Selling Consumer Products That Increase Mortality...mentioning
confidence: 99%
“…The following supporting information can be downloaded at : Figure S1: An example of alcohol aisles in a national retail pharmacy in the US; Figure S2: The number of sugar-sweetened beverages sold through 75 pharmacies belonging to a national pharmacy chain. The plot was generated based on data published in [ 154 ]; Table S1: CHRs from five different review articles used to create a graph shown in Figure 4 .…”
mentioning
confidence: 99%